Rediscovery of the ant genus Amyrmex Kusnezov (Hymenoptera: Formicidae) and its transfer from Dolichoderinae to Leptanilloidinae - Ward, Philip S.; Brady, Seán G. (Zootaxa, 2009)
The ant genus Amyrmex Kusnezov (1953), previously known only from several males collected more than fifty years ago in Tucumán, Argentina, is redescribed on the basis of more recent material from Argentina and Brazil. Using DNA sequence data from seven nuclear genes we investigate the phylogenetic position of Amyrmex and demonstrate that it is a member of the subfamily Leptanilloidinae, rather than the Dolichoderinae to which it had been previously assigned. This placement is also supported by a reevaluation of morphological traits. Amyrmex is possibly a senior synonym of the worker-based genus Asphinctanilloides Brandão, Diniz, Agosti & Delabie (1999), but additional study is needed to establish generic limits within the Leptanilloidinae and to reliably associate male and worker castes.